2008
DOI: 10.1039/b800185e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viscoelasticity on the flow pattern and the volumetric flow rate in electroosmotic flows through a microchannel

Abstract: Many lab-on-a-chip based microsystems process biofluids such as blood and DNA solutions. These fluids are viscoelastic and show extraordinary flow behaviors, not existing in Newtonian fluids. Adopting appropriate constitutive equations these exotic flow behaviors can be modeled and predicted reasonably using various numerical methods. In the present paper, we investigate viscoelastic electroosmotic flows through a rectangular straight microchannel with and without pressure gradient. It is shown that the volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…This may be due to the interference of the pressure gradient on the electroosmotic flow profile of non-Newtonian fluid leading to origin of some sort of secondary flows. 62 Since, physiological fluids exhibit shear thinning behavior, the assisting flow should be preferred on account of enhanced mass transfer.…”
Section: Effect Of Operating Conditions On the System Performancementioning
confidence: 99%
“…This may be due to the interference of the pressure gradient on the electroosmotic flow profile of non-Newtonian fluid leading to origin of some sort of secondary flows. 62 Since, physiological fluids exhibit shear thinning behavior, the assisting flow should be preferred on account of enhanced mass transfer.…”
Section: Effect Of Operating Conditions On the System Performancementioning
confidence: 99%
“…Furthermore, they presented a comprehensive review of electrokinetics pertaining to non-Newtonian fluids [11]. Park and Lee [12] derived a semi-analytical expression for the Helmholtz-Smoluchowski velocity under pure electroosmosis conditions for the full Phan-ThienTanner (PTT) constitutive equation, and they used a finite volume method to calculate numerically the flow of the full PTT model in a rectangular duct under the action of electroosmosis and a pressure gradient [13]. With the help of a Fourier transform, Bandopadhyay and Chakraborty [14] investigated the dynamical interplay between interfacial electrokinetics and a combined dissipative and elastic behavior of flow in narrow confinements.…”
Section: Introductionmentioning
confidence: 99%
“…Figs. [15][16][17][18] indicate that with an increase in the value of S, which is the ratio of the suction velocity to the Helmholtz-Smoluchowski electro-osmotic velocity U HS , neither the steady state value nor the amplitude of oscillation of velocity, u, suffer any significant change. However, Figs.…”
Section: Results and Discussion: A Representative Case Studymentioning
confidence: 99%
“…Some further discussions on EOFs actuated by the application of electrokinetic forces are available in [10][11][12][13][14]. Park and Lee [15] presented an analysis of the problem of EOF of a viscoelastic fluid on a straight rectangular microchannel with-/-without pressure gradient. They observed that the volumetric flow rate of a viscoelastic fluid differs significantly from that of a Newtonian fluid under the action of the same pressure gradient-/-externally applied electric field.…”
Section: Introductionmentioning
confidence: 99%